2010
DOI: 10.1016/j.jpeds.2010.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Remission of Sleep-Disordered Breathing and Related Symptoms in 6- to 17-Year Old Children—The Tucson Children's Assessment of Sleep Apnea Study

Abstract: Objective-To determine the incidence and remission of sleep disordered breathing in adolescent children.Study design-319 children completed two home polysomnograms approximately 5 years apart. Sleep disordered breathing (SDB) was determined to be present if a child had a respiratory disturbance index ≥ 1 event per hour associated with a ≥3% oxygen desaturation. Subjective symptoms such as witnessed apnea, excessive daytime sleepiness, difficulty initiating and maintaining sleep, and habitual loud snoring were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 28 publications
8
63
1
7
Order By: Relevance
“…Step 3: recognition of factors predicting long-term persistence of obstructive SDB Literature review a-d) Risk factors for persistence of untreated OSAS were identified in three prospective, cohort studies (class I) [125][126][127].…”
Section: Literature Review A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Step 3: recognition of factors predicting long-term persistence of obstructive SDB Literature review a-d) Risk factors for persistence of untreated OSAS were identified in three prospective, cohort studies (class I) [125][126][127].…”
Section: Literature Review A)mentioning
confidence: 99%
“…Treatment has been shown to be beneficial to children at risk of persistent OSAS (male sex, obese, with persistent tonsillar hypertrophy) (class I and III) [126,127,183]. c) A positive respiratory polygraphy or nocturnal oximetry in the context of clinical symptoms indicative of obstructive SDB has been used as an indication for adenotonsillectomy (class III or IV) [136,162,184].…”
Section: 4mentioning
confidence: 99%
“…In the NANOS study, children with persistent mild OSAS had a significant increase in BMI during the period of dietary modifications [19]. Similarly, in the prospective Tuscon's Children's Assessment of Sleep Apnea Study (TuCASA), untreated participants with persistent OSAS or new-onset disease had increased risk for rising BMI percentile or development of obesity during transition from childhood to adolescence [20]. In a population-based cohort from Hong Kong, persistence of overweight/obesity status over an average period of 4.6 years was a significant predictor of primary snoring progression to OSAS [21].…”
Section: Obese Children With Osas Frequently Have Unfavourable Responmentioning
confidence: 99%
“…10 The routine use of TþA as treatment for symptoms of obstructive sleep-disordered breathing is even more controversial in view of a recent publication on the natural history of pediatric OSA. 11 Over a 5-year period, OSA (AHI 1 episode/hr) and excessive daytime sleepiness resolve spontaneously in approximately 70% and 60%, respectively, of preadolescent children.…”
Section: Letter To the Editormentioning
confidence: 99%